KADIN ISTIHDAMININ TÜRKIYE'DEKI 12 BÖLGEYE GÖRE ISTATISTIKSEL YÖNTEMLERLE ANALIZI - YILMAZ, GÜL (Fırat Üniveristesi, 2023)
Kadınların iş gücü piyasasına girmeleri ve piyasada istikrarlı olarak üretim yapmaları ekonomik kalkınma açısından önemli bir etkendir. Kadın istihdamının Türkiye'deki mevcut durumunu Türkiye İstatistik Kurumu (TÜİK) istatistikî bölgeleri bazında incelemek amacıyla yapılan bu çalışmada, kadının iş gücü piyasası içerisindeki yeri TÜİK'den elde edilen veriler yardımıyla incelenmiştir. Türkiye'de kadınların iş gücü, istihdam ve işsizlik durumları, yaşları ve eğitimleri dikkate alınarak bölgelere göre analiz edilmiştir..

It is an important factor for economic development that women enter the labor market and produce consistently in the market. In this study, which was carried out to examine the current situation of women's employment in Turkey on the basis of statistical regions of the Turkish Statistical Institute (TUIK), the place of women in the labor market was examined with the help of data obtained from TUIK. The labor force, employment and unemployment status of women in Turkey have been analyzed by region, taking into account their age and education.
Analysis of women's employment by statistical methods by 12 regions in Turkey
Keywords: İstatistik